Spatial Heterogeneity of Soil Fractal Characteristics and Its Influencing Factors in Sugan Lake Wetland at the Northern Margin of the Tibetan Plateau - Haolin Li; Zhao, Xiawei; Zhao, Chengzhang; Zhang, Lu; Ma, Xinyu; Wang, Yan (Eurasian soil science, 2025)
The study of the spatial distribution pattern of soil fractal properties and its relationship with water-salt factors contributes to an in-depth understanding of the mechanisms by which the ecohydrological processes of inland salt marsh wetlands affect soil texture. In the wetland of Sugan Lake at the northern margin of the Qaidam Basin on the Tibetan Plateau, the single and multiple fractal dimensions and their influencing factors of four sample sites with different hydrological gradients from the lake shore to the peripheral uplands of Xiaosugan Lake were analyzed by combining field investigation and quantitative analysis. The results showed that from the lake shore to the peripheral uplands of Xiaosugan Lake, the soil texture demonstrate clear multifractal behaviour, with generalized dimension and multifractal singularity spectra showing inverse S-type curves and left-deviating. The degree of heterogeneity of soil textural homogeneity and particle size distribution frequency curves decreased and then increased, and the soil singularity fractal dimensions ( D v ), capacity dimensions ( D 0 ), information dimensions ( D 1 ), correlation dimensions ( D 2 ), singular spectrum width Δα, and singular spectrum shape feature Δ f showed U-shaped trends. Soil D v , D 0 , D 1 , D 2 , Δα, and Δ f were positively correlated with clay content, silt content, vegetative belowground biomass (BGB), and Ca 2+ , negatively correlated with the soil sodium adsorption ratio (SAR). Under the combined influence of wetland hydrological characteristics, ionic composition, and plant community characteristics, the soil fractal dimension of the Sugan Lake wetland showed a complex distributional evolution pattern, reflecting the interactive influence mechanism between soil structure and wetland biotic and abiotic factors in inland salt marsh wetlands.